Ciência e imagem: processos criativos de produção de conteúdos visuais para a divulgação científica do projeto ARCA do CEP - Araujo, Tatiana Maria Soares (Universidade Federal de São Carlos, 2023)
The research has as its theme the Pernambuco Endemism Center, the Alagoas curassow and the research, conservation and environmental education actions of CEP's ARCA project. The CEP is a territory of the Brazilian northeastern Atlantic Forest that suffers from high levels of degradation, being one of the most threatened and least researched environments in the world. In this ecosystem, endemic species are constantly threatened, many of which are already extinct in the area. The Alagoas curassow (Pauxi Mitu) is an endemic bird that has been extinct in the region for 40 years and has survived only in breeding grounds. In 2019, it was reintroduced to CEP through an unprecedented partnership between several institutions and scientific projects, such as CEP's ARCA project — of which this research is part. The objects of research investigation are the practical-theoretical creative processes that produced visual and audiovisual content for CEP's ARCA project — which uses these materials for scientific dissemination. The study has applied methodology, qualitative research and phenomenological approach. The theoretical foundation is based on Image Theory, with emphasis on Gestalt and Peirce's semiotics, and on contemporary communicational studies and their influences on science education. As a result of the research, for the graphic dissemination front, a logo and a visual identity were developed for CEP's ARCA project, using digital design techniques. For the project's filmic dissemination front, short documentary videos were made about the history of the Alagoas curassow and its reintroduction to the CEP — the Eu, Mutum series, using cinematographic montage and editing techniques.
Science and Image: practical-theoretical creative processes for the production of visual content for the scientific dissemination of the ARCA do CEP project
Keywords: Centro de Endemismo Pernambuco; Mutum-de-alagoas; Processos Criativos; Divulgação Científica; Imagem; Pernambuco Endemism Center; Alagoas curassow; Creative Processes; Scientific divulgation; Image; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS SOCIAIS APLICADAS::COMUNICACAO; CIENCIAS SOCIAIS APLICADAS::COMUNICACAO::COMUNICACAO VISUAL